Curricular planning and its influence on the development of the four basic skills of the english language at “Daniel Alvarez Burneo” high school.period 2010-2011 - Carrión Sánchez, Silvio Roberto (2012)
The research worked named: “CURRICULAR PLANNING AND ITS INFLUENCE ON THE DEVELOPMENT OF THE FOUR BASIC SKILLS OF THE ENGLISH LANGUAGE AT “DANIEL ALVAREZ BURNEO” HIGH SCHOOL, PERIOD 2010-2011”, whose general objective is “to determine how the curricular planning influences on the development of the four basic linguistic skills of the English Language at “Daniel Alvarez Burneo” High School, Period 2010-2011.” To accomplish this research we took advantage of the scientific, analytical-synthetic, explicative, inductive-deductive methods. To collect the key information we made use of the survey which were directed to teachers and students. The research group set up three hypotheses:the development of the four basic skills of the English Language is influenced by the different aspects of the curricular planning, the teachers do not make the meso-planning according to the established goals in the macro-planning of the English area; and the micro-planning influences on the development of the four basic linguistic skills of the English Language at “Daniel Alvarez Burneo” High School, period 2010-2011. Both were proved according to the got results and the respective analysis made by the research group. The surveys applied to teachers and students showed that the teachers do not make the respective planning in order to accomplish the objectives of the curricular planning.The micro-planning is overlooked by the teachers and students could notice that, most of the students confirmed that they do not follow a procedure, they improvise and there is a waste of time. Due to the lack of planning the four basic skills are affected, they are not developed in an effective way. It is necessary a good lesson planning including all the key elements. Students said that teachers apply just a few strategies and they are not as useful as they should be. That is why, the research group proved that the curricular planning influences directly on the development of the four basic skills.